Organizational Culture and Employees Performance in Uganda National Drug Authority Tororo - Ajore Salume (Uganda Christian University, 2024)
The study investigated the relationship between Organizational Culture and employee performance within Uganda National Drug Authority Tororo. It was guided with specific objectives that include; examining the relationship between organizational values and employee performance, the relationship between organizational beliefs on employee performance, and establishing the relationship between of organizational practices on employeeperformance. The study employed a population of 24 and a sample size of 23 respondents, using Solomon's formula to ensure statistical reliability. The primary objective is to explore how organizational values, beliefs, and practices influence employee performance, Findings indicate significant correlations between organizational values and enhanced employee performance, emphasizing the pivotal role of shared principles in promoting productivity. The study also highlights how organizational beliefs, when aligned with core convictions, foster employee engagement and commitment. Additionally, effective organizational practices are identified as key drivers of improved employee performance, underscoring the importance of supportive work environments. In conclusion, the research asserts that a robust organizational culture at Uganda National Drug Authority Tororo significantly enhances employee performance, recommending the reinforcement of values, beliefs, and practices that resonate with employee expectations. Furthermore, the study advocates for ongoing enhancements in organizational practices to sustain high performance levels and employee satisfaction. Future research should further explore other dimensions of organizational culture and its impact on employee behaviour, including the interaction between leadership styles, organizational culture, and employee motivation, offering potential avenues for enhancing organizational effectiveness and employee well-being.